Properties and hydrolysis action on cassava starch of some microbial amylases - Anh, Hoang Kim; Suong, Ngo Ke; Lien, Nguyen Xich (Academia Journal of Biology, 2015)
Amylase is one of the most important industrial enzymes in Biotechnology. This study deals with the investigation of some main properties of amylases from Bacillus and Aspergillus (Institute of Tropical biology), such as the MW, the temperature, the pH opt, the Ca2+ effect, the hydrolysis action towards different substrates, as well as the profile of starch hydrolyzed products.